2018
DOI: 10.1186/s12943-018-0873-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLEU1 contributes to colorectal cancer progression via activation of KPNA3

Abstract: BackgroundAccumulating evidences show that long noncoding RNAs (lncRNA) play essential roles in the development and progression of various malignancies. However, their functions remains poorly understood and many lncRNAs have not been defined in colorectal cancer (CRC). In this study, we investigated the role of DLEU1 in CRC.MethodsQuantitative real-time PCR was used to detect the expression of DLEU1 and survival analysis was adopted to explore the association between DLEU1 expression and the prognosis of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 42 publications
5
102
0
Order By: Relevance
“…14 For example, lncRNA DLEU1 promoted CRC cell progression through regulating KPNA3. 15 Moreover, lncRNA CRNDE induced cell proliferation and chemoresistance in CRC. 16 lncRNA BANCR has been determined to relate to CRC poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…14 For example, lncRNA DLEU1 promoted CRC cell progression through regulating KPNA3. 15 Moreover, lncRNA CRNDE induced cell proliferation and chemoresistance in CRC. 16 lncRNA BANCR has been determined to relate to CRC poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, many lncRNAs have been reported to play important roles in multiply biological processes of osteosarcoma including tumour cell proliferation, invasion, migration, and chemoresistance [3,4]. LncRNA DLEU1 is overexpressed and exerts an oncogene function by regulating cell proliferation, migration and invasion in several types of cancers including bladder cancer [6], cervical cancer [7], oral squamous cell carcinoma [8], non-small cell lung cancer [9], and colorectal cancer [10]. However, the role of DLEU1 in osteosarcoma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm the possible permeability of these peptide oligomer functions in gliomas, we chose DLEU1 for subsequent simulations. DLEU1 activates KPNA3, which is related to the increased proliferation and migration of cancer cells 53 . Some reports have indicated that DLEU1 can increase cell proliferation; our results showed that ORF1 and ORF8 in DLEU1 could encode small TM peptides.…”
Section: Discussionmentioning
confidence: 99%